Studi Literatur: Telefarmasi oleh Farmasi Komunitas: Telepharmacy Literature Study by Community Pharmacy - Andriana, Tanti (Jurnal Surya Medika (JSM), 2023)
Telepharmacy ia an increasingly popular healthcare service, involving pharmacists in multidisciplinary healthcare teams. Undoubtedly, telepharmacy is a great opportunity to improve health management in the community. Despite its popularity in some countries, the overall clinical impact of telepharmacyl services is currently unable to be fully documented due to a lack of available studies. This literature review aims to provide an overview of telepharmacy studies by community pharmacies. This literature review was written using a scoping review approach. The literature search used the Google Scholar and PudMed databases for the 2018-2022 time period. Based on the results of a study on 12 articles that met the requirement, it can be concluded that telepharmacyl services have proven to have a positive impact in the form of reducing errors, side effects, length of stay, and costs. Regulations issued support pharmacists in providing telepharmacy sevices. However, telepharmacy also faces several obstacles such as infrastructure and technology barriers, organizational and financial barriers, policy and regulatory barriers and cultural barriers